Combine <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> and <math><mstyle displaystyle="true"><mfrac><mrow><mn>1</mn></mrow><mrow><mn>3</mn></mrow></mfrac></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> from both sides of the inequality.

Subtract <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> from <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> .

Divide each term in <math><mstyle displaystyle="true"><mo>-</mo><mfrac><mrow><mi>x</mi></mrow><mrow><mn>3</mn></mrow></mfrac><mo><</mo><mo>-</mo><mn>2</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> . When multiplying or dividing both sides of an inequality by a negative value, flip the direction of the inequality sign.

Simplify the left side.

Dividing two negative values results in a positive value.

Divide <math><mstyle displaystyle="true"><mfrac><mrow><mi>x</mi></mrow><mrow><mn>3</mn></mrow></mfrac></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Simplify the right side.

Divide <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> .

Multiply both sides by <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> .

Simplify the left side.

Cancel the common factor of <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Simplify the right side.

Multiply <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> .

Do you know how to Graph -1/3x+5<3? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.